Comparative study of different clean-up techniques for the determination of λ-cyhalothrin and cypermethrin in palm oil matrices by gas chromatography with electron capture detection - Muhamad, H.; Zainudin, B.H.; Abu Bakar, N.K. (2012)
Solid phase extraction (SPE) and dispersive solid-phase extraction (d-SPE) were compared and evaluated for the determination of Î»-cyhalothrin and cypermethrin in palm oil matrices by gas chromatography with an electron capture detector (GC-ECD). Several SPE sorbents such as graphitised carbon black (GCB), primary secondary amine (PSA), C 18, silica, and florisil were tested in order to minimise fat residues. The results show that mixed sorbents using GCB and PSA obtained cleaner extracts than a single GCB and PSA sorbents. The average recoveries obtained for each pesticide ranged between 81 and 114 at five fortification levels with the relative standard deviation of less than 7 in all cases. The limits of detection for these pesticides were ranged between 0.025 and 0.05 Î¼g/g. The proposed method was applied successfully for the residue determination of both Î»-cyhalothrin and cypermethrin in crude palm oil samples obtained from local mills throughout Malaysia.